Effect of a combination of Phaseolus vulgaris L. extract and acarbose on postprandial glucose level after cooked rice intake in healthy volunteers (Medical Journal of Indonesia, 2009)
Aim This study was aimed to measure the effects of combination Phaseolus vulgaris extract and acarbose compared to acarbose alone on postprandial glucose concentration in healthy volunteers after cooked rice intake. Methods Blood sample were obtained at several time points up to three hours after cooked rice intake. The parameter for postprandial glucose concentration is the area under the curve (AUC) of glucose concentration vs.time for three hours after cooked rice intake. Results After taking this combination, postprandial glucose concentration was reduced by 21.6%, while the reduction by acarbose alone was 22.9%. Conclusions The reduction of postprandial glucose concentration after administration of this combination was not significantly different compared to that after administration of acarbose alone. (Med J Indones 2009; 18: 25-30) Keywords: Phaseolus vulgaris extract, acarbose, postprandial glucose concentration